Instruments for measuring empowering patient education competence of nurses: Systematic review - Eskolin Silja-Elisa; Inkeroinen Saija; Leino-Kilpi Helena; Virtanen Heli (Wiley, 2025)
Aim: This review aimed to identify validated self-reported instruments used to measure nurses' competence or attribute(s) of competence in empowering patient education, to describe their development and main content and critically appraise and summarize the quality of the instruments.
Design: Systematic review.
Data Sources: Electronic databases of PubMed, CINAHL and ERIC were searched from January 2000 to May 2022.
Review Methods: Data was extracted following predetermined inclusion criteria. With the support of the research group, two researchers performed data selection and appraised the methodological quality using the COnsensus- based Standards for the selection of health status Measurement INstruments checklist (COSMIN).
Results: A total of 19 studies reporting 11 instruments were included. The instruments measured varied attributes of competence and the contents were heterogenous reflecting the complex nature of both empowerment and competence as concepts. Overall, the reported psychometric properties of the instruments and methodological quality of the studies were at least adequate. However, there was variation in the testing of the instruments' psychometric properties and lack of evidence limited the evaluation of both the methodological quality of the studies and quality of instruments.
Conclusion: The psychometric properties of the existing instruments assessing nurses' competence in empowering patient education need to be tested further, and future instrument development should be built on a clearer definition of empowerment as well as on more rigorous testing and reporting. In addition, continued efforts to clarify and define both empowerment and competence on the conceptual level are needed.
Impact: Evidence on nurses' competence in empowering patient education and its valid and reliable assessment instruments is scarce. Existing instruments are heterogenous and are often missing proper testing of validity and reliability. These findings contribute to further research on developing and testing the instruments of competence in empowering patient education and strengthening nurses' empowering patient education competence in the clinical practice.